Technical Writing for Environmental Engineers. - Coolidge Toker, Emily (Environmental engineering collection., 2018)
There are many kinds of writing required in the workplace, and a degree of mastery is necessary for effective and efficient communication between colleagues, clients, and managers. This book is meant to serve as a guide and tool for engineers navigating formal and informal writing in the workplace. Topics include the most common types of technical documents, the fundamentals of professional writing, the use of references and citations, and how and why engineers and other professionals should always proofread their work.